2015
DOI: 10.1016/j.tube.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Mycobacterium tuberculosis isolated from tuberculosis patients in the Serengeti ecosystem in Tanzania

Abstract: SummaryThis study was part of a larger cross-sectional survey that was evaluating tuberculosis (TB) infection in humans, livestock and wildlife in the Serengeti ecosystem in Tanzania. The study aimed at evaluating the genetic diversity of Mycobacterium tuberculosis isolates from TB patients attending health facilities in the Serengeti ecosystem. DNA was extracted from 214 sputum cultures obtained from consecutively enrolled newly diagnosed untreated TB patients aged ≥18 years. Spacer oligonucleotide typing (sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 34 publications
9
36
1
Order By: Relevance
“…Similar families have been reported in variable proportions in other countries bordering Tanzania [31e35], indicating a geographical widespread of this group of spoligotypes in the region. These findings are also in agreement with those of other studies conducted in Tanzania which reported the predominance of these families [21,36,37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar families have been reported in variable proportions in other countries bordering Tanzania [31e35], indicating a geographical widespread of this group of spoligotypes in the region. These findings are also in agreement with those of other studies conducted in Tanzania which reported the predominance of these families [21,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Strain families previously reported in Tanzania but not reported in this study include the Haarlem genotype [21,37] and the X genotypes [21,36e38]. We detected a high proportion of T family isolates as found in previous studies [21,37].…”
Section: Discussionsupporting
confidence: 81%
“…Of the 472 culture isolates from sputum samples, 214 (45.3%) M. tuberculosis strains were isolated and no M. bovis was recovered. Other results regarding M. tuberculosis have been reported separately (Mbugi et al., ).…”
Section: Resultsmentioning
confidence: 83%
“…However, several studies found that the increase in MTBC virulence was associated with a decreased and/ or delayed inflammmatory response, possibly as a result of considerable bacterial proliferation in the early stages of infection and leading to increased MTBC virulence in the final stages. (5,6) The Bacille Calmette-Guérin (BCG) vaccine, which was developed almost 100 years ago and has been shown to prevent severe forms of TB in children, is still widely used. However, there is currently no vaccine that is effective in preventing TB disease in adults, either before or after exposure to TB infection.…”
Section: Department Of Physiology Faculty Of Medicine Trisakti Univementioning
confidence: 99%